2017
DOI: 10.1016/j.cmet.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The FGF21-CCL11 Axis Mediates Beiging of White Adipose Tissues by Coupling Sympathetic Nervous System to Type 2 Immunity

Abstract: Type 2 cytokines are important signals triggering biogenesis of thermogenic beige adipocytes in white adipose tissue (WAT) during cold acclimation. However, how cold activates type 2 immunity in WAT remains obscure. Here we show that cold-induced type 2 immune responses and beiging in subcutaneous WAT (scWAT) are abrogated in mice with adipose-selective ablation of FGF21 or its co-receptor β-Klotho, whereas such impairments are reversed by replenishment with chemokine CCL11. Mechanistically, FGF21 acts on adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
119
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 51 publications
6
119
2
Order By: Relevance
“…During the long‐term fasting, hepatokine FGF21 is upregulated to directly target adipose tissue to facilitate fat utilization and activate the ketogenesis signaling (Badman et al , ; BonDurant et al , ; Fisher et al , ; Huang et al , ). In addition, FGF21 overexpression results in a variety of abnormalities including female infertility, circadian behavior disruption and bone loss (Bookout et al , ; Owen et al , ; Wei et al , b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the long‐term fasting, hepatokine FGF21 is upregulated to directly target adipose tissue to facilitate fat utilization and activate the ketogenesis signaling (Badman et al , ; BonDurant et al , ; Fisher et al , ; Huang et al , ). In addition, FGF21 overexpression results in a variety of abnormalities including female infertility, circadian behavior disruption and bone loss (Bookout et al , ; Owen et al , ; Wei et al , b).…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05 and **P < 0.01 by unpaired Student's t-test. the ketogenesis signaling (Badman et al, 2009;BonDurant et al, 2017;Fisher et al, 2012;Huang et al, 2017). In addition, FGF21 overexpression results in a variety of abnormalities including female infertility, circadian behavior disruption and bone loss Owen et al, 2013;Wei et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite of the fact that transcription of adiponectin was remarkably induced within white adipose tissue upon cold challenge [67], such a change was not abolished adipose-specific deletion of FGF21 or its co-receptor β Klotho [75], indicating that cold-evoked upregulation of adiponectin in adipose tissue was not controlled under FGF21. Moreover, although adiponectin deficient mice were also less sensitive to white adipose browning stimulated by cold [67,76], it seems that it activates browning remodeling in distinct ways as FGF21.…”
Section: Fgf21-adiponectin Axis In Cold Adaptationmentioning
confidence: 91%
“…Recently it is found that FGF21 expression was also strongly upregulated in white adipocytes under cold-acclimated conditions [75]. By using the adipocyte-specific FGF21 knockout mice, it was further revealed that adipocytederived FGF21 acts in an autocrine manner to promote the expression and secretion of CCL11 via activation of ERK1/2 [75]. This event then drives recruitment of eosinophils into subcutaneous WAT, leading to increases in accumulation of M2 macrophages, and proliferation/commitment of adipocyte precursors into beige adipocytes.…”
Section: Fgf21-adiponectin Axis In Cold Adaptationmentioning
confidence: 99%
“…This route of action has been proposed as a major endocrine axis of FGF21 for insulin sensitization; lowering of systemic glucose, triacylglycerol, and LDL; fighting against obesity, diabetes, fatty liver diseases, hyperlipidemia, and associated comorbidities; and achieving metabolic health [2,73,74,107]. Some of these effects are likely mediated by adipokines, such as CCL11 and adiponectin, as shown in mice [108,109]. In cold-induced nonshivering thermogenesis or exercise stress condition, BAT also becomes a source of endocrine FGF21 in a β-adrenergicand cAMPdependent manner, which in turn facilitates mitochondrial genesis, oxidative capacity, uncoupling, and heat generation, leading to adaptation to cold conditions and core body temperature maintenance [110][111][112].…”
Section: Fgf21 Metabolic Axismentioning
confidence: 99%